Efektivitas Pijat Bayi Terhadap Berat Badan Pada Bayi Dengan Berat Badan Lahir Rendah: Literature Review - Khairunisa, Nabila; Purnawati , IGA Dewi (Maternal & Neonatal Health Journal, 2025)
Infants with Low Birth Weight have a high risk of growth disturbances and complications. Infant massage is a non-pharmacological intervention proven to increase weight through stimulation of the nervous system, improved appetite, and enhanced nutrient absorption. This literature review aims to determine the effectiveness of infant massage in increasing weight among low birth weight infants. The method used was a literature review by searching for articles through the Google Scholar database from 2020 to 2025. A total of five articles met the inclusion criteria and were analyzed. The results showed that infant massage significantly increased the weight of low birth weight infants when performed routinely for 10–14 days. The techniques used varied; however, all studies reported a significant increase. In conclusion, infant massage is proven to be effective as a complementary therapy to increase weight in infants with low birth weight